2011
DOI: 10.3177/jnsv.57.355
|View full text |Cite
|
Sign up to set email alerts
|

Pups of Dams Fed Low-Fat Diet during Pregnancy and Lactation Showed Strong Preference for High-Fat Diet to Achieve Optimal Growth

Abstract: SummaryTo investigate the causes why pups of dams fed a low-fat high-carbohydrate diet (LFD) showed a strong preference for fat, three groups of dams were fed one of three diets during pregnancy and lactation: the LFD, a control diet (CTD) or a high-fat low-carbohydrate diet (HFD). After weaning, pups of each of the three groups were divided into two equal subgroups (Pair 1 and Pair 2), for a total of six pup subgroups. Each subgroup was placed on a two-choice diet program of the LFD and the HFD (Pair 1), or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…palmitate and stearate, to monounsaturated FAs, palmitoleate oleate, which are the predominant substrates for triglyceride synthesis observed in pups from mothers fed high-fat diet during lactation (23) . Other mechanisms observed in Wistar rats fed cafeteria diet was the expression of metabolism genes as such, Slc27a3, a fatty acid transporter was 9.6-fold higher in visceral adipose tissue and 6.3-fold lower in subcutaneous adipose tissue of cafeteria group compared to standard-diet fed rats indicating a epigenetic programming (24) . As a limitation, in this study we did not investigate cellular mechanisms, but we did observe consistent phenotypic changes in pups derived from mothers fed a low-energy diet followed by an obesogenic diet and changes in phenotypic expression is strong indicator that several underlying cellular mechanisms occur.…”
Section: Discussionmentioning
confidence: 90%
“…palmitate and stearate, to monounsaturated FAs, palmitoleate oleate, which are the predominant substrates for triglyceride synthesis observed in pups from mothers fed high-fat diet during lactation (23) . Other mechanisms observed in Wistar rats fed cafeteria diet was the expression of metabolism genes as such, Slc27a3, a fatty acid transporter was 9.6-fold higher in visceral adipose tissue and 6.3-fold lower in subcutaneous adipose tissue of cafeteria group compared to standard-diet fed rats indicating a epigenetic programming (24) . As a limitation, in this study we did not investigate cellular mechanisms, but we did observe consistent phenotypic changes in pups derived from mothers fed a low-energy diet followed by an obesogenic diet and changes in phenotypic expression is strong indicator that several underlying cellular mechanisms occur.…”
Section: Discussionmentioning
confidence: 90%
“…As a result of the energy density (kcal/g) diets, consumption may or may not differ between the groups. Earlier studies have shown a reduction in the maternal diet intake during the perinatal period, with the consumption of calories equal or greater, depending of the energy density of the diet [31][32][33]. Other studies indicate that hyperphagia in the mothers is associated with an inhibition of the hypothalamic satiety factors; the circulation levels of leptin were observed to increase on this type of diet, but appeared to trigger resistance to its action and thus contribute to the delay in satiety [28,34].…”
Section: Discussionmentioning
confidence: 97%